Effect of Hyaluronidase Addition to Lidocaine for Trigger Point Injection in Myofascial Pain Syndrome. Issue 8 (7th October 2015) - Choi, Ji Won; Lee, Chul Joong; Lee, Sangmin M.; Shin, Byung Seop; Jun, Byunghui; Sim, Woo Seog
Abstract: Introduction: This randomized, double‐blind study compared the efficacy of hyaluronidase co‐injection with that of local anesthesia alone on the degree of pain and quality of life in patients with myofascial pain syndrome (MPS). Methods: Sixty‐one adults, aged 25 to 75 years, with MPS affecting both trapezius muscles were randomly assigned to one of the 2 treatment groups: lidocaine (group L: n = 31) or hyaluronidase (group H: n = 30). All patients received Trigger point injection (TPI). Group L received 3.2 mL 0.5% lidocaine alone. Group H received the same solution of lidocaine mixed with hyaluronidase (600 iu/mL). Patients were followed for 14 days (pre‐ and post‐TPI days 0, 1, 4, 7, and 14) with the verbal numerical rating scale (VNRS), and the primary outcome was VNRS on day 7. Also, we evaluated the neck disability index (NDI) and the short form of brief pain inventory (BPI‐SF) on pre‐ and post‐TPI day 14. Results: In both groups, VNRS decreased on days 4, 7, and 14 compared to the pre‐TPI. However, in group H, VNRS decreased on day 1 also. There were no significant differences of VNRS between the 2 groups during 14 days. NDI and BPI‐SF scores also significantly decreased after TPI in both groups. Conclusions: There were no significant differences between groups in terms of VNRS, NDI, or BPI‐SF scores. However, TPI consisting of lidocaine mixed with hyaluronidase worked more effectively than lidocaine alone on post‐TPI day 1. Further, hyaluronidase showed a tendency to reduce TPI‐related soreness.